Prevalence of Stigma among Medical Care Providers towards Patients with Schizophrenia and Obsessive Compulsive Disorders - Elamin, Mohamed Osman; Badri, Hatim Matooq; Khan, Wahaj A. (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: This study aimed to identify the stigma among medical care providers towards people with Schizophrenia and Obsessive-Compulsive Disorder and the factors associated with increased stigma among them. METHODOLOGY: A cross-sectional study design was used to determine the prevalence of stigma among medical professionals toward patients with Schizophrenia and obsessive-compulsive disorders (OCD). Participants were from one of the best hospitals in Makkah, Saudi Arabia, King Abdullah Medical City (KAMC), in which 283 of their medical care providers were randomly selected using the RAOSOFT calculator technique. All medical care providers at King Abdullah Medical City were included. Medical care providers who refused to participate were excluded. Data entered, cleaned, and analyzed using the Statistical Package for Social Sciences (SPSS) Version 22. RESULTS: The study clarified that medical care providers have less stigmatization towards patients suffering from OCD (53%) than their stigma towards patients with Schizophrenia (54.4%). The study found that (26.4%), and (1.4%) of physicians felt comfortable dealing with OCD and schizophrenic patients, respectively, while (28.2%) and (11.2%) of nurses felt comfortable dealing with OCD and schizophrenic patients, respectively. CONCLUSION: The study concluded that the stigma towards patients with Schizophrenia is higher than it is towards patients with OCD; this stigma is higher among physicians than nursing staff. KEYWORDS: Cross-sectional, Stigma, Schizophrenia, Obsessive-compulsive disorder (OCD), Medical care providers, Medical City.